2006
DOI: 10.1093/jmedent/43.1.104
|View full text |Cite
|
Sign up to set email alerts
|

Natural Infection of Culex theileri (Diptera: Culicidae) with Dirofilaria immitis (Nematoda: Filarioidea) on Madeira Island, Portugal

Abstract: Field and laboratory studies were performed to verify whether Culex theileri Theobald functions as a natural vector of Dirofilaria immitis (Leidy) on Madeira Island, Portugal. CO2-baited light traps (EVS traps) were use to sample mosquitoes monthly basis between February 2002 and February 2003 in the area of Quebradas (Funchal). Three mosquito species were captured, including 58 Culex pipiens L., 790 Cx. theileri, and three Culiseta longiareolata (Macquart). Only C. theileri tested positive for D. immitis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 2 publications
1
21
0
1
Order By: Relevance
“…For this reason, this finding, together with the report in Madeira island [8], implies a dirofilariosis transmission complexity in Southern Europe markedly higher than that considered so far. However, higher vector potential of a mosquito species in a region or in different regions could be elucidated by ecological factors such as geographical features, season a climate, and also host preference of mosquito species [56].…”
Section: Discussionmentioning
confidence: 46%
See 4 more Smart Citations
“…For this reason, this finding, together with the report in Madeira island [8], implies a dirofilariosis transmission complexity in Southern Europe markedly higher than that considered so far. However, higher vector potential of a mosquito species in a region or in different regions could be elucidated by ecological factors such as geographical features, season a climate, and also host preference of mosquito species [56].…”
Section: Discussionmentioning
confidence: 46%
“…Nevertheless we cannot ruled out that most abundant captures, both of Cx. theileri and other culicid species could reveal higher prevalences like other studies have demonstrated (to 8.6% have been cited in different mosquito species have demonstrated [8,9,[45][46][47].…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations